A Critical Appraisal of Peter Gowans Contemporary Intra-Core Relations and World-Systems Theory: A Capitalist World-Empire or U.S.-East Asian Geo-Economic Integration? - John Gulick (Journal of World-Systems Research, 2015)
This paper evaluates Peter Gowans musings on the topic of a U.S.-centered capitalist world-empire. Gowans heterodox concept of a capitalist world-empire is intellectually defensible. And his claim that U.S. hegemony is historically unique, because unlike previous dominant powers the U.S. has been able to distinctly mold the accumulation regimes and security environments of its would-be rivals in the core, is more than convincing. However, Gowan tends to overstate the degree to which the U.S. in the 1990s enjoyed a productive sector revival, rather than a mere super-inflation of dollar-denominated assets. This tendency prevents him from anticipating just how summarily the U.S. would ditch consensual approaches to managing the capitalistworld-economy once the Wall Street bubble collapsed, and hence from appreciating just how fed up Western European and East Asian elites would become with the predatory character of U.S. hegemony in decay. In conclusion the paper argues that while the U.S. may have neither the resources nor the credibility to politically control the global division of labor, something akin to a U.S.-East Asian geo-economic bloc may be in the process of forming. This is so because the Chinese and Japanese economic growth models remain wedded to the underwriting of the U.S. seigniorage privileges', and because past and present frictions between China and Japan stand in the way of tighter Sino-Japanese political coordination.